1998
DOI: 10.1007/s11881-998-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of multisensory structured language instruction for at-risk foreign language learners: A comparison study of high school Spanish students

Abstract: In this study, the benefits of multisensory structured language (MSL) instruction in Spanish were examined. Participants were students in high-school-level Spanish attending girls" preparatory schools. Of the 55 participants, 39 qualified as at-risk for foreign language learning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 23 publications
4
35
0
2
Order By: Relevance
“…As opposed to such nonexplicit FL teaching approaches, research has shown that so-called multisensory structured learning (MSL) approaches are effective ways to meet native, FL and SL learning needs of dyslexics Miller & Bussman Gillis, 2000;Nijakowska, 2008;Schneider, 1999Schneider, , 2009Sparks et al, 1998). These studies represent consistent results regarding the effect of MSL instruction.…”
Section: The Role and Impact Of Instruction And Interventionmentioning
confidence: 80%
“…As opposed to such nonexplicit FL teaching approaches, research has shown that so-called multisensory structured learning (MSL) approaches are effective ways to meet native, FL and SL learning needs of dyslexics Miller & Bussman Gillis, 2000;Nijakowska, 2008;Schneider, 1999Schneider, , 2009Sparks et al, 1998). These studies represent consistent results regarding the effect of MSL instruction.…”
Section: The Role and Impact Of Instruction And Interventionmentioning
confidence: 80%
“…In a multi-sensory foreign language program, students with learning disabilities have been shown to benefit from being engaged more fully, with multiple sensory inputs or expressions involved in learning tasks (Sparks et al, 1998). Logically, the same premise can be applied to assessments rooted in the curriculum; if the instruction is multi-sensory, the assessment should be, too.…”
Section: General Multisensory Considerationsmentioning
confidence: 99%
“…However, the multi-sensory nature of principles developed by Orton and Gillingham, coupled with evidence that multi-sensory methods benefit students with SLDs learning new langauges (Sparks et al, 1998) could make the application of the Gillingham method to a second language a starting point for instruction and assessment. The Gillingham method used a technique called simultaneous oral spelling, in which a teacher says a spelling word, and the student repeats the word, names the individual letters while writing them, and then says the word (Gillingham & Stillman, 1997).…”
Section: General Multisensory Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sparks and Ganschow (1993) determined that a multi-sensory approach to teaching phonological skills improved the phonemic awareness of students in both Spanish and English. Further research has centered on multi-sensory instruction incorporating explicit phonological teaching (Ganschow & Sparks, 1995), and a two-year study of at-risk students indicated that a multi-sensory approach promoted performance comparable to peers instructed with traditional methods (Sparks et al, 1998). Because of demands in working memory and diverse functioning of the CNS which can affect second language learning (Kormos & Safar, 2008;Palladino & Cornoldi, 2004), multi-sensory approaches have been promoted by Dal (2008) and Sousa (2001) and supported by the research of Amend et al (2009).…”
Section: Multi-sensory Approachesmentioning
confidence: 99%